Inez Eaves interviewed by John Meredith for the John Meredith folklore collection - Eaves, Inez, 1916-; Meredith, John, 1920-2001. (1985)
Folkloric recording. Inez Eaves plays hohner Erica accordion and speaks of local dancing.
Accordion: 1. Quickstep, Five minutes more -- Conversation: Inez Eaves speaks of tunes played at dances, learning tunes, dances in applesheds -- Accordion: 2. Daisy bell, 3. My bonnie lies over the ocean, 4. Schottische, Ring the bell, 5. Schottische, The Prince of Wales (prior to this Eaves briefly described dance steps for the tunes), 6. Waltz medley, I belong to Glasgow, Over the waves, 7. Schottische (ex Harry Colsons of Scotts Road), 8. Barndance, Grab your girl (ex Laurie Thorpes), 9. Polka, Early in the morning, 10. Waltz, Two little girls in blue.
Recorded at Geeveston, Tasmania on November 19, 1985.
Also available online
Timed summary available.
Keywords: Eaves, Inez, -- 1916- -- Interviews; Accordion music; Folk dance music -- Australia